Synthesis of Embelin-Fe complex from Embelia ribes fruits and characterization. (2021) - Arthanareeswari, M.; Harshil, H.D.; Ganesh, M.R.; Mohankumar, R.
Highlights: Embelin was isolated from the fruits of the traditionally used medicinal plant Embelia ribes. . An Embelin-Fe complex was prepared at room temperature following a simple scheme. The compound was isolated using conventional column chromatography. Its purity was confirmed using NMR, IR and Mass spectroscopy. Abstract: Herbal medicine has been used for the prevention and treatment of various health ailments from time immemorial. Embelia Ribes fruits contain several chemical constituents like Embelin, volatile oil, fixed oil, resin, tannin, Christem Bine (Alkaloid) and phenolic acids like Caffeic acid etc. In the present work, Embelin (2, 5-dihydroxy-3- undecyl-p-benzoquinone), is one of the active chemical constituents which is present in the Embelia ribes fruits with known activities was extracted using chloroform solvents and isolated through column chromatography techniques. An Embelin-Fe complex was generated using the isolated Embelin. The synthetic method employed for generating the Embelin-Fe complex was simple and room temperature based. The generated complex is expected to have applications including increased bio activity, as well as possible catalytic potential.